Cutting edge: A comparison of contemporary practices of riparian buffer retention around headwaters in Canada, Finland and Sweden - Kuglerova, Lenka; Muotka, Timo; Richardson, John (Swedish University of Agricultural Sciences, 2020)
These data describe 286 small streams in Canada, Sweden and Finland and the conditions of their riparian buffers. All the study streams were subject to forest harvest between 2010 and 2016 and riparian buffers were left by forest practitioners. We measured number of stream physical properties (size, substrate, channel forms) and the conditions of the associated riparian buffers (width, tree composition, age structure). We further assessed other impairments caused by forestry operations such as machine tracks in the riparian area, drainage ditches connected to the streams, and stream crossing. Those data are also available in the database.

Table S3. The separately uploaded table contains data which were used for analyzing riparian buffer widths and the factors affecting it (catchment area, riparian slope and clearcut size), as well as Impairment Index for all sites in all three countries. Table S4-S6. These separately uploaded tables contain all data from the Canadian, Finnish and Swedish sites used in the study, including information on the buffer width and composition, stream properties, impairments, site names, site information and buffer functions.

Dessa data beskriver 286 små vattendrag i Kanada, Sverige och Finland och deras kantzoner. Alla vattendrag har varit under avverkning mellan 2010 och 2016 och kantzoner lämnades. Vi mätte antalet fysiska vattendragsegenskaper (storlek, underlag, geomorfiska former) och villkoren för tillhörande kantzoner (bredd, trädsammansättning, åldersstruktur). Vi bedömde vidare andra skogsbruksstörningar som maskinspår i bäcknära zoner, diken anslutna till vattendrag och strömningskorsning. Alla dessa data finns också tillgängliga i databasen.

Se engelska katalogsidan för mer information: https://snd.gu.se/en/catalogue/study/SND1125
Cutting edge: En jämförelse av kantzoner längs små vattendrag i Kanada, Finland och Sverige
Keywords: flowing water; rinnande vatten; water analysis; vattenanalys; buffer zone; buffertzon; rivers/streams; floder/åar; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi